Tingkat Permudaan Vegetasi Pada Habitat Burung Kakatua-kecil Jambul Kuning (Cacatua sulphurea parvula) di Desa Kuanfatu Kabupaten Timor Tengah Selatan - Asteria Milla Radjang; Fadlan Pramatana; Oki Hidayat; Maria M. E. Purnama (Wana Lestari, 2026)
Birds are a group of vertebrates that play a vital role in ecosystems that support natural forest regeneration. One such species is the Yellow-crested Cockatoo. This bird is protected in Indonesia by Government Regulation and is categorized as critically endangered based on IUCN data. Kuanfatu Village is one of the areas that provides habitat for Cockatoos. This area is not a conservation area, but there are efforts to protect cockatoos through a traditional ceremony called Saeba Banu. This study aims to determine the level of vegetation regeneration in the cockatoo habitat. Data collection used a combination of methods, namely the strip and quadrant transect methods, and data analysis included vegetation analysis, namely the calculation of the Important Value Index (INP). The results showed that the vegetation in this area was dominated by Swietenia mahagoni at the seedling level with an INP of 90.11% and at the sapling level with an INP of 98.61% for the Swietenia mahagoni species.